Deletion of Registration and Identification of the Motorized Vehicle in the Perspective of Human Rights - Risang Pujiyanto; Sonny Taufan (Universitas Kuningan, 2020)
This research aims to review and analyze the provisions on the deletion of registration and identification of motorized vehicles data for the owners of motorized vehicles who do not re-register at least 2 (two) years after the validity period of the motorized vehicle number is expired in the perspective of Human Rights and provide prescriptions on the provisions referred to. This research is normative research by using statute approach. The results of the study found that motorized vehicle ownership is a Human Rights which is included in the category of derogable rights. The deletion of motorized vehicle data is a limitation of Human Rights and is regulated in Act Number 22/2009 about Traffic and Road Transport. However, the aforementioned limitation has the potential to be incompatible with the purpose of the limitation as stipulated in the Constitution of the Republic of Indonesia. Reviewing the provisions of Article 74 paragraph (3) of Act No. 22/2009 and implementation of the national program of changed motorized vehicle ownership, needs to be prioritized, so that the objectives of the motorized vehicle registration provisions can be achieved and will ultimately increase revenue from motorized vehicle tax. Penghapusan Registrasi dan Identifikasi Kendaraan Bermotor dalam Perspektif Hak Asasi Manusia Penelitian ini bertujuan mengkaji dan menganalisis ketentuan penghapusan registrasi dan identifikasi kendaraan bermotor bagi pemilik kendaraan bermotor yang tidak melakukan registrasi ulang sekurang-kurangnya 2 (dua) tahun setelah habis masa berlaku Surat Tanda Nomor Kendaraan Bermotor dalam perspektif Hak Asasi Manusia dan memberikan preskripsi atas ketentuan dimaksud. Penelitian ini merupakan penelitian normatif dengan menggunakan pendekatan undang-undang. Hasil penelitian menemukan bahwa kepemilikan kendaraan bermotor merupakan Hak Asasi Manusia yang termasuk dalam kategori derogable rights. Penghapusan data kendaraan bermotor diatur dalam Undang-Undang Nomor 22 Tahun 2009 dan telah sesuai dengan ketentuan pembatasan Hak Asasi Manusia ditetapkan dalam suatu Undang-Undang, namun pembatasan dimaksud berpotensi tidak sesuai dengan tujuan pembatasan yaitu Ketertiban Umum. Peninjauan ulang ketentuan Pasal 74 ayat (3) Undang-Undang Nomor 22 Tahun 2009 dan penyelenggaraan program balik nama kendaraan bermotor secara nasional perlu diprioritaskan agar tujuan ketentuan registrasi kendaraan bermotor dapat tercapai dan pada akhirnya akan meningkatkan pendapatan dari pajak kendaraan bermotor.